2015
DOI: 10.11648/j.ajap.20150403.15
|View full text |Cite
|
Sign up to set email alerts
|

Body Integrity Identity Disorder: Development and Evaluation of an Inventory for the Assessment of the Severity

Abstract: Body Integrity Identity Disorder (BIID), the wish of subjects for an amputation of otherwise healthy limbs, is a rare disturbance. Until now, BIID was seen as a symptom affecting a group of people suffering from an urging desire for amputation. But while some of the BIID-affected people only have a weak wish for an amputation others show severe symptoms. The aim of this work was the development of a psychological test to measure the severity of the wish for amputation or palsy in BIID afflicted subjects. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
(11 reference statements)
0
10
0
1
Order By: Relevance
“…Applying the ReHI in individuals with Xenomelia may recreate the reported feeling of disownership -or, by inducing disownership over an unwanted limb -create a cessation in the dysphoric feeling of overcompleteness. Similar to the pretend behaviour exercised by these individuals (First, 2005;L. Fischer, 2015), this may offer a temporary relief, if not a treatment.…”
Section: Limitations and Future Directionsmentioning
confidence: 95%
“…Applying the ReHI in individuals with Xenomelia may recreate the reported feeling of disownership -or, by inducing disownership over an unwanted limb -create a cessation in the dysphoric feeling of overcompleteness. Similar to the pretend behaviour exercised by these individuals (First, 2005;L. Fischer, 2015), this may offer a temporary relief, if not a treatment.…”
Section: Limitations and Future Directionsmentioning
confidence: 95%
“…Applying the ReHI in individuals with Xenomelia may recreate the reported feeling of disownershipor, by inducing disownership over an unwanted limbcreate a cessation in the dysphoric feeling of over-completeness. Similar to the pretending behaviour exercised by these individuals (First, 2005;L. Fischer, 2015), this may offer a temporary relief, if not a treatment.…”
Section: Limitations and Future Directionsmentioning
confidence: 96%
“…The results of the BIID screening instrument for severity and intensity from Fischer were transformed into arithmetic means which were classified in accordance with the standard values developed by Fischer [11,12]. The sample of this study showed variations from very low up to medium extents of severity of Xenomelia.…”
Section: Resultsmentioning
confidence: 99%
“…The Hamburg Compulsive Inventory (short form; originally named: "Hamburger Zwangsinventar", [31]), the Body Integrity Identity disorder screening instrument for severity and intensity from M. Fischer [11,12]. Because none of the existing obsessive-compulsive screening instruments captures the specific typical compulsive behaviour of Xenomelia affected people, it was necessary to develop an own questionnaire named "Questionnaire for detecting non-specific compulsive behavior" ("Fragebogen zur Erfassung unspezifischen zwanghaften Verhaltens; FzEuzV").…”
Section: Inventory Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation